IMPLEMENTASI KOMPETENSI PEDAGOGIK GURU SD NEGERI 2 KUALA BARU ACEH SINGKIL - Nurhaidah Nurhaidah. (Jurnal Pesona Dasar, 2019)
This study, entitled implementation of the competence of Pedagogic Teacher SD Negeri 2 Kuala Baru Aceh Singkil. This research aims to know the Pedagogy Teacher SD Negeri 2 New Aceh Singkil Kuala. The approach used in this study is qualitative and descriptive research types. Subjects in the study were 14 teachers in SD Negeri Kuala Baru Aceh Singkil. Data collection is done by observation techniques. All data processed with the next stage of the analysis the qualitative data, namely data reduction, data model (Data Display), and withdrawal/verification conclusion. Data that have been obtained are then analyzed using descriptive percentage formula. The results of this research show that the implementation of the competency of the Pedagogy in SD Negeri 2 Kuala Baru Aceh Singkil  already belongs, although there are some constraints experienced by the teachers. It is seen from the competence on aspects of the planning, execution and control of learning. Less teacher plan well the learning activities will be undertaken and methods/approaches to learning that are used are conventional teacher. Pedagogic competence is the ability of teachers in managing learning learners, and a teacher of skills related to the study of the interaction between teacher and student which includes an understanding of learners as an understanding of the nature, characteristics, and development of children in the process of teaching and learning in terms of providing material or evaluations in order to actualize the various potential learners.